(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The study of this topic is of very wide interest, both from the scientific intelligentsia and from the political elite. Civil society is considered a measure of the level of development. This is especially true of the post-Soviet countries, which only appeared on the world map just over twenty years ago. In the Soviet Union, the very concept of civil society was not used in relation to Soviet society. The newly independent states faced the need to develop their own conceptual foundations for building a civil society that adequately meets the needs of their development in the changed conditions. Taking into account the heterogeneity of the composition and the divergence of the political and socio-economic aspirations of the new states, the nature and dynamics of the processes of building civil society developed in them in different ways. In a number of other countries, the events in the post-Soviet period were characterized by acute drama, up to the outbreaks of the so-called color revolutions, which radically changed the political structure of society and the guidelines of socio-economic development in them.